2003
DOI: 10.1159/000073314
|View full text |Cite
|
Sign up to set email alerts
|

Predation Experiments on Infant Spectral Tarsiers (Tarsius spectrum)

Abstract: In this paper, I investigate how mother and infant spectral tarsiers, Tarsius spectrum, respond to the presence of potential predators. I conducted this study at Tangkoko Nature Reserve in Sulawesi, Indonesia, from June to November 1999. I exposed 2 infants to 3 types of potential predators (large models of birds of prey, large rubber snakes and the vocalizations of large birds of prey) for a total of 18 nights. Infants moved a greater distance from their parked location when exposed to rubber snakes (1.8 m) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 34 publications
(37 reference statements)
0
26
0
Order By: Relevance
“…The fact that infant tarsiers less than a week old alarm-called in response to snakes, even if they had never encountered them before provides further evidence against this cultural transmission hypothesis [Gursky, 2003[Gursky, , 2006. Gursky [2006] also argues that her results -specifically the fact that the extragroup males recruited to mobbing events are not bigger than resident males -provide evidence against the 'attract the mightier' hypothesis.…”
Section: Spectral Tarsiersmentioning
confidence: 95%
See 1 more Smart Citation
“…The fact that infant tarsiers less than a week old alarm-called in response to snakes, even if they had never encountered them before provides further evidence against this cultural transmission hypothesis [Gursky, 2003[Gursky, , 2006. Gursky [2006] also argues that her results -specifically the fact that the extragroup males recruited to mobbing events are not bigger than resident males -provide evidence against the 'attract the mightier' hypothesis.…”
Section: Spectral Tarsiersmentioning
confidence: 95%
“…Both observational and experimental studies of snake mobbing have been used to provide insight into the function of predator harassment in spectral tarsiers [Gursky, 2002[Gursky, , 2003[Gursky, , 2005[Gursky, , 2006[Gursky, , 2007. Gursky [2006] found that tarsiers did not always mob the snakes they encountered; mobbing was observed in only 11 of 43 encounters with real snakes (25%) and in 31 of 73 encounters (42%) with model snakes.…”
Section: Spectral Tarsiersmentioning
confidence: 99%
“…They give early-morning family choruses, scentmark preferentially along the boundaries of their territory and regularly engage in territorial disputes with neighboring groups. Consequently, they exhibit minimal overlap between neighboring territories [Gursky, 2003]. Spectral tarsier home ranges vary from 1.6 to 4.1 ha with an average of 2.3 ha for females and 3.1 ha for males [Gursky, 2003].…”
Section: Study Speciesmentioning
confidence: 99%
“…Consequently, they exhibit minimal overlap between neighboring territories [Gursky, 2003]. Spectral tarsier home ranges vary from 1.6 to 4.1 ha with an average of 2.3 ha for females and 3.1 ha for males [Gursky, 2003]. Spectral tarsiers also exhibit a tremendous amount of site fidelity.…”
Section: Study Speciesmentioning
confidence: 99%
“…In their work, Cheney and Seyfarth [Cheney and Seyfarth, 1996;Seyfarth and Cheney, 1997] show that call referents and behavioral contingencies appear important for successful communication (see also Gursky [2003] for mother-infant calls in spectral tarsiers). The current work employs quantitative techniques suited to (1) identification of patterns or sequences of behavior of an individual and (2) testing of whether those patterns are important predictors of behavioral outcomes of another individual [Gottman and Bakeman, 1979;Bakeman and Quera, 1995;Bakeman and Gottman, 1997].…”
mentioning
confidence: 99%